Development of Sensor-Based Blind Swimmig Aids - Hartono, Fajar Vidya; Tangkudung, James; Sukur, Abdul; Dlis, Firmansyah (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Blindness is a condition where the senses of vision are not functioning (low vision) or overall (total blindness). Persons with visual impairments are who can enjoy swimming with the help of sensors. The aim of the study was to create aids for sensor-based blind visual swimming that can be used during swimming exercises. The method used is a qualitative approach, the main data obtained through observation, questionnaires, interviews, and documentation and procedures of research and development used is the Borg and Gall model. This study is expected to contribute to blind swimming aids material products which are effectively used for swimming exercise skills. This study concluded that the product development sensor based blind learning swimming aids can be used for motion skills training for blind swimming athletes.